Management of radiation proctopathy: a focus on the role of endoscopy. (1st February 2019) - McGoran, John J; Robinson, Richard
Abstract : Chronic radiation proctopathy (CRP) affects a significant proportion of patients who undergo radiation treatment for cancer. It manifests in many ways, including pain, diarrhoea and rectal bleeding. It is often with rectal bleeding and related problems, such as anaemia, that these individuals present to the endoscopy department. Various treatments do exist for CRP. They include medical therapies, such as sucralfate or formalin enemas, endoscopic treatment and surgical intervention, which is reserved for refractory cases. Argon plasma coagulation (APC) is the mainstay of endoscopic treatment, but it can carry risks of ulceration and stricture formation. In response to this, other endoscopic therapies, such as radiofrequency ablation (RFA) and cryotherapy, have been proposed and tried. This clinical review explores the available evidence and provides a guide to the decision-making process that a member of the endoscopy team may undergo in order to achieve a satisfactory outcome for the patient.